Kansei Engineering Approach in Software Interface Design - Isa, Indra Griha Tofik (Universitas Pakuan, 2018)
User satisfaction is a major factor in designing a product. Technically it can be realized explicitly how the product is designed according to the needs of its users. There are other factors that influence the success of the product, the psychological value of the user who can implicitly become a parameter in product design. But the thing that becomes a constraint is how to translate these psychological factors into the parameters of product design. Kansei Engineering (KE) is one approach in product design that involves the user's psychological side and how to translate the cognitive aspects of the user into the product of the design proposal. The KE methods, the one discussed in this study, is Kansei Engineering Type 1 (KEPack), which involves several multivariate analyzes. The conclusion of this research is how KE in designing a product, not only industrial product, but KE can be involved in matters related to Human Computer Interaction, especially interface design. Keywords: Product Development, Kansei Engineering, Kansei Engineering Type 1 (KEPack)